Electrochemical detection of kynurenic acid in the presence of tryptophan with the carbon paste electrode modified with the flower-like nanostructures of zinc oxide doped with terbium - Amir Poursaeed, Ali; Jahani, Shohreh; Moradalizadeh, Mehran; Shahidi Zandi, Mehdi; Foroughi, Mohammad Mehdi (Frontiers in Chemistry, 2023)
With the help of a hydrothermal approach in this study, we could provide flower-like nanostructures (NSs) of zinc oxide (ZnO) doped with Tb (FL-NS Tb3+/ZnO). Then, FL-NS Tb3+/ZnO morphology was investigated by EDX, SEM, XRD, and map analysis. Results revealed higher activity centers and porosity of this nanocomposite, which were followed by acceptable electrochemical function. Hence, it can be utilized for fabricating an electrochemical sensor with appropriate response for simultaneous determination of kynurenic acid (KYN) and tryptophan (TRP). On the other hand, as compared with the modified carbon paste electrode (FL-NS Tb3+/ZnO/CPE), the bare carbon paste electrode (BCPE) exhibit weak response toward KYN and TRP but the modified electrode was followed by high current response for KYN and TRP at a potential 0.35 and 0.809 V. Therefore, cyclic voltammetry (CV) was applied in optimal experimental conditions to study the electrochemical behaviors of KYN and TRP over the surface of the proposed modified electrode. Moreover, we used differential pulse voltammetry (DPV) for quantitative measurements. It could be said that this new modified electrode linearly ranged 0.001 and 700.0 μM, with the detection limit of 0.34 nM and 0.22 nM for KYN and TRP. In addition, KYN and TRP in real samples could be analyzed by this sensor, with the recovery 97.75 –103.6% for the spiked KYN and TRP in real samples.